Motivations to Teach: A Significance in Enhancing Hiring Measures of Pre-Service TVET Teachers - Eze, Nicholas Ude; Osondu, Stella; Nwosu, Fidelia Ogochukwu; Anorue, Honesta Chidiebere; Nwadi, Calister; Chilaka, Akuchinyere (Journal of Technical Education and Training, 2022)
This study investigated the underlying factors that influence potential TVET teachers’ decision to pursue a teaching career in order to recruit more teachers. The motivation of pre-service TVET graduates obtaining a postgraduate diploma in technical education was therefore investigated using the QUAN-QUAL approach to collect quantitative data via a researcher-created, self-administered questionnaire and qualitative data via written essays and narratives using the triangulation mixed method design. Participants were selected from two cohorts (N=78) of students enrolled in the various departments for the Postgraduate Diploma in Technical Education (PGDTE) program of the University of Nigeria. According to the quantitative analysis, excellent role models from previous teachers, the demanding nature of the job role, a willingness to impart relevant knowledge and skills, a willingness to assist financially disadvantaged students in gaining marketable job skills, and the country’s presumed demand for TVET teachers were the primary motivators for pre-service teachers. The qualitative analysis found seven (7) themes, three of which were motivational: desire to assist students and community/sharing expertise; personal dream/calling/passion to teach; and the desire to financially aid students who are incapacitated. However, the gender aspect revealed that male and female pre-service TVET teachers showed significant differences in their altruistic and intrinsic impulses. Following that, the two sets of data were compared and investigated. The ramifications of the findings were then examined, as well as their significance in enhancing hiring measures through setting of standards for tech-voc education programs to improve on the status of TVET teachers to attract quality graduates of technical education programs who can teach as TVET teachers before and after completing their programs.